MODIFICATIONS TO THE BOUNDARIES OF THE NATURAL PLAGUE FOCI IN THE VOLGA-URAL INTERFLUVE - A. A. Kuznetsov; A. N. Matrosov; A. M. Porshakov; V. N. Chekashov; M. M. Shilov (Проблемы особо опасных инфекций, 2017)
Objective of the study is to locate the present-day sites and sizes of the natural plague foci in the Volga-Ural Interfluve. Materials and methods. According to the results of the field and office mapping, 2015 in the Volga-Ural steppe and sandy plague foci, designed have been electronic maps of the sectors situated in the periphery. Results and conclusions. During the past 3–4 decades significant decrease in plague enzooties in the territory of the Volga-Ural Interfluve has been observed. It occurs due to the plowing and melioration of the grazing lands. It is established that the southern and south-western outskirts of enzootic territories have natural boundaries represented with the linear elements of hydrography, and the eastern ones are the state border of the Russian Federation and the Republic of Kazakhstan. At sites where suitable linear elements of the landscape are absent (up north and west) the frames of the sectors, where evidence of enzooty is retained, are used as the formal external boundaries. Widespread plowing of semi-desert area made the territories in the eastern part of the Volgograd Region inadequate for small souslik habitation, which marks the loss of plague enzooty features. This fact in its turn led to the reduction of steppe focus acreage by 30 %, the coverage being currently 20873 km2 . Configuration of the sandy focus changed little, if at all, and amounts to 8625 km2 . Registering of the actual position and sizes of natural plague foci within the strictly set boundaries put on topographic maps provides for targeted planning and complex prophylactic anti-plague measures. New spatial indicators of natural plague foci are formalized in official normative-methodological documents regulating epidemiological surveillance over plague.